2009
DOI: 10.2176/nmc.49.427
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Masquerading as a Hypertensive Putaminal Hemorrhage: A Diagnostic Pitfall -Case Report-

Abstract: A 58-year-old man presented with a rare case of glioblastoma masquerading as intracerebral hemorrhage (ICH). He had been medicated for hypertension and diabetes for 10 years before collapsing at home. Brain computed tomography (CT) showed ICH in the right putamen, but CT with contrast medium showed no underlying lesion. He was treated initially with intravenous administration of anti-hypertensive agent under a diagnosis of hypertensive putaminal hemorrhage. ICH aspiration surgery was performed, and serial CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…However, high attenuation on CT and varying T1 intensity on MR imaging for acute hematoma can mask enhancing lesions of ICH on CT and MR imaging. 11,12 Previous studies 13,14 showed that dual-energy CT improves detection of enhancement within highly attenuated hemorrhage, but dual-energy CT or even single-energy contrast-enhanced CT and MR imaging are not always used as the initial imaging technique in patients with acute ICH. Serial follow-up with NECT takes time to confirm complete ICH resolution and might cause diagnostic delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high attenuation on CT and varying T1 intensity on MR imaging for acute hematoma can mask enhancing lesions of ICH on CT and MR imaging. 11,12 Previous studies 13,14 showed that dual-energy CT improves detection of enhancement within highly attenuated hemorrhage, but dual-energy CT or even single-energy contrast-enhanced CT and MR imaging are not always used as the initial imaging technique in patients with acute ICH. Serial follow-up with NECT takes time to confirm complete ICH resolution and might cause diagnostic delay.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] However, enhancement of secondary ICH can be obscured by surrounding high attenuation or various T1 signal intensities from hematoma; these make diagnosis of secondary ICH difficult. [10][11][12] Dual-energy CT offers better differentiation between ICH of tumor and nontumor etiology because of better visualization of the enhancing lesion within a high-attenuation hemorrhage. 13,14 However, dual-energy CT is less available than single-energy CT.…”
mentioning
confidence: 99%
“…5,13,14 However, acute ICH has a high attenuation on CT, which may mask contrast enhancement. 15 Although MR imaging may be more useful in detecting underlying tumors in patients with tumor bleeding, 5,13,16 acute ICH may show variable high signals on T1-weighted images, making it difficult to differentiate enhancement from high-signal-intensity hematoma. 13,16,17 DECT can differentiate bone and iodine and hematoma and iodine.…”
mentioning
confidence: 99%
“…In contrast, if the tumors are compressed by a large hemorrhage, or the border between the tumors and hemorrhage is unclear, intratumoral hemorrhage may be indistinguishable from spontaneous ICH, even though contrast material is used3). Thus, a CT with contrast cannot exclude underlying pathologies that may cause ICH, especially if the patient has a history of hypertension, and the location is typical for hypertensive ICH.…”
Section: Discussionmentioning
confidence: 99%